Synthesis, characters and application of silver-doped cabon Nanotubes and nanoporous polymers for purification of water samples - Rananga, Lutendo Evelyn (University of Limpopo (Turfloop Campus), 2013)
Drinkable water is water that is safe enough to be consumed by humans or used with low risk of immediate or long term harm. World-wide, insufficient access to portable water and use of sources contaminated with disease vectors, pathogens, and unacceptable levels of toxins is a huge problem. The use of such water for drinking and food preparation leads to the widespread of acute and chronic illnesses. This is a major cause of death and misery in many undeveloped countries. Reduction of waterborne diseases is a major public health goal in developing countries. Nanotechnology offers the possibility of an efficient removal of pollutants and microorganisms from water. Essentially, three classes of nanoscale materials were investigated as functional materials for water purification in this study. Silver nanoparticles, carbon nanotubes and beta ()-cyclodextrin polymers were synthesised and characterised specifically for purification of water samples. β-cyclodextrin is soluble in both water and other aqueous media. In order to render cyclodextrins insoluble, they were converted into highly cross-linked polymers, by polymerisation with a bifunctional linker, hexamethylene diisocyanate. Cyclodextrins were functionalised and synthesised with either the allyl or the benzoyl group. Characterisation with fourier transform infrared (FTIR) spectrophotometer confirmed the functionalisation process. Thereafter the scanning electron microscopy (SEM) analysis confirmed the polymers’ morphology to be spongy, and capable of absorbing contaminants. Multi-walled carbon nanotubes (MWCNTs) were treated with a mixture of sulphuric and nitric acid in order to introduce the carboxyl and hydroxyl groups. These were characterised by SEM, transmission electron microscopy (TEM), X-ray diffraction (XRD) and FTIR spectroscopy to confirm the functionalisation process. Silver nanoparticles were synthesised from sodium citrate and silver nitrate, using sodium dodecyl sulphate as a surfactant. Their characterisation was done by SEM, energy dispersive X ray (EDX) spectroscopy, TEM, UV/Vis spectroscopy and XRD to confirm a face centred cubic structure with an estimated crystallite size ranging from 50 to 100 nm.β-cyclodextrin polymers, functionalised multi-walled carbon nanotubes and silver nanoparticle-doped MWCNTs/cyclodextrin composites were characterised by SEM, TEM, XRD, Brunauer-Emmet-Teller (BET) and EDX. Analysis of the phenolic compound, 4-hydroxynitrobenzene in water, using these nanocomposites, demonstrated good capabilities of removing organic contaminants from water samples as indicated by their high absorption efficiencies of the contaminants. The synthesised metal-organic composites were tested for their effectiveness in removing organic contaminants as well as for eliminating Escherichia coli bacteria from water. The synthesised composites presented up to 97% absorption efficiency of organic contaminants and up to 100% inactivation of the bacteria. There was complete destruction of bacteria from the water analysed at various times and varying concentrations. After a long exposure of the nanocomposites to E. coli, pits were noticeable on the external morphology of the bacteria, thus suggesting that the nanocomposites are bactericidal. The bacterial activity increased with temperature,when studied between 10 oC and 30 oC.
Thesis (MSc. (Chemistry)) -- University of Limpopo, 2013
Keywords: Synthesis; Characterization and application; Nanotechnology; Carbon nanotubes; Nanochemistry; Water -- Purification